A literatura Infantil e a expressão dramática: um estudo com crianças - Figueiredo, Ana Isabel da Silva (2024)
O estudo que se apresenta de seguida foi realizado o âmbito da unidade curricular Prática de Ensino Supervisionada em Educação Pré-escolar e em 1.º Ciclo do Ensino Básico inserida no Mestrado em Educação Pré-escolar e Ensino do 1.º Ciclo do Ensino Básico, da Universidade de Évora, sob o tema A Literatura Infantil e a Expressão Dramática: um estudo com crianças. A metodologia aplicada durante o estudo, feito aos longo das práticas nos dois contextos, foi a investigação-ação e teve como principal objetivo promover nas crianças a educação literária e a expressão dramática, interrelacionando-as. O enquadramento teórico foi realizado com base no conhecimento e experiência de vários autores, dentro da educação literária e da expressão dramática e nos documentos oficiais de orientação curricular que servem de base à planificação, ação e avaliação por parte dos professores do 1.º Ciclo do Ensino Básico e dos Educadores de Infância, assim como o Plano Nacional de Leitura e o Plano Nacional das Artes. Este estudo dá-nos conta de que são inúmeras as evidências que nos mostram a interrelação entre a educação literária e a expressão dramática; - Children`s Literature and Dramatic Expression: one study in childhood Abstract: The study presented below was carried out within the domain of the curricular unit Supervised Teaching Practice in Pre-school Education and 1st Cycle of Basic Education included in the Master's Degree in Pre-school Education and Teaching of the 1st Cycle of Basic Education, from the University of Évora, under the theme Children's Literature and Dramatic Expression: a study with children. The theoretical framework was created based on the knowledge and experience of several authors, within literary education and dramatic expression and on official curricular guidance documents that serve as a basis for planning, action, and evaluation by teachers of the 1st Cycle of Basic Education and Early Childhood Educators, as well as the National Reading Plan and the National Arts Plan evidence that shows us the interrelationship between literary education and dramatic expression. The methogology applied the study, carried out throughout the practices in both contexts, was action-research and its main objective was to promote literary education and dramatic expression in children, and interrelating them. The theoretical framework was created based on the knowledge and experience of several authors, within literary education and dramatic expression and on official curricular guidance documents that serve as a basis for planning, action, and evaluation by teachers of the 1st Cycle of Basic Education and Early Childhood Educators, as well as the National Reading Plan and the National Arts Plan. This study shows us that there is countless evidence that shows us the interrelationship between literary education and dramatic expression.